2x(2x+3x)-3x=14

Simple and best practice solution for 2x(2x+3x)-3x=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(2x+3x)-3x=14 equation:



2x(2x+3x)-3x=14
We move all terms to the left:
2x(2x+3x)-3x-(14)=0
We add all the numbers together, and all the variables
2x(+5x)-3x-14=0
We add all the numbers together, and all the variables
-3x+2x(+5x)-14=0
We multiply parentheses
10x^2-3x-14=0
a = 10; b = -3; c = -14;
Δ = b2-4ac
Δ = -32-4·10·(-14)
Δ = 569
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-\sqrt{569}}{2*10}=\frac{3-\sqrt{569}}{20} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+\sqrt{569}}{2*10}=\frac{3+\sqrt{569}}{20} $

See similar equations:

| z-235=176 | | -8x+5+2x=-13 | | 3y-47=y+27 | | 2x+13-3x=x+5 | | 10r+8=18 | | 27=x(5)-x(2) | | x+19=-x-17 | | -10x+6=10-4x | | -9x+7+10x=24 | | 12(4x-1)=372 | | -4(10n-6)=-406 | | 45x+67=45x+78 | | 11=u/27 | | 9=30-7r | | 5m+2=-3m-6 | | 2(4x+13)=130 | | 5m+2=–3m–6 | | 6x+3=3-6x | | 880=-22q | | 7+4=-4r+6+4r-1 | | 0=224t-16t2 | | 112=19x | | 5a+3(a+3)-a=a | | k/4=25 | | (4x)=24 | | 95=-8x=14 | | 5m=–45 | | 1.2x^2-0.7x-22.4=0 | | 3^(x-3)=15 | | (5x)=120 | | 7x4=11 | | J5+2j=7 |

Equations solver categories